PENGEMBANGAN MEDIA FLIPCHART BERTEMAKAN KELESTARIAN ALAM UNTUK MENGOPTIMALKAN KECERDASAN NATURALIS ANAK DI TKIT ZIA SALSABILA MEDAN - Nurul Zahriani Jf; Sukiman Sukiman (AWLADY : Jurnal Pendidikan Anak, 2020)
The focus of this research is the development of a natural sustainability-themed Flipchart media conducted to optimize the child's naturalistic intelligence. The research model is R&D (Research and Development) by Borg and Gall. The implementation procedure uses six steps. The results of the development of Flipchart media in the theme of natural sustainability are generally declared feasible. It is based on the validation results of material experts acquired value of 92%, the media experts are 78%, and a learning practitioner (class teacher) 86%. The results of the effectiveness test gained from field trials were obtained average pretests score of 56.53 and average posttest score of 87.73. Then, based on the results of the analysis Test t acquired t observes of 16.965 and t table of 1.761 (t observation > t table). The results showed a significant difference in the level of optimization of the naturalistic intelligence development of child B Group in TK IT Zia Salsabila Medan before and after using Flipchart media. So, it was concluded that flipchart media with the theme of natural preservation was appropriate and effective as a medium to optimize the naturalistic intelligence of early childhood in TKIT Zia Salsabila Medan.Keywords:  Development, flipchart, naturalistic intelligence of children